1 The use and impact of 12-lead electrocardiograms in acute stroke patients: a systematic review. (21st May 2017) - Munro, S; Quinn, T; Cooke, D; Joy, M
Abstract : Aim: Stroke is a leading cause of mortality and disability across the globe. Emergency Medical Services assess and transport a large number of these patients in the prehospital setting. Guidelines for UK ambulance services recommend recording a 12-lead electrocardiogram in the prehospital environment, providing this does not add to significant delay in transporting the patient to hospital; however, this recommendation is not based on any evidence. Methods: A systematic review was conducted to search and synthesise the literature surrounding the use of prehospital electrocardiograms in acute stroke patients, focusing on the prevalence of abnormalities and their association with prognosis and outcome. Online databases, references from selected articles and hand searches were made to identify eligible studies. Two authors independently reviewed the studies to ensure eligibility criteria were met. Main outcomes were presence of abnormality on electrocardiogram, mortality and disability. No studies set in the prehospital environment were found by the search; therefore the eligibility criteria were widened to include hospital-based studies. A total of 18 studies were subsequently included in the review. Results: Although the prevalence of electrocardiogram abnormalities appears common in hospitalised patients, their prognostic impact on mortality, disability and other adverse outcomes is conflicting amongst the literature. There is a lack of research surrounding the use of prehospital electrocardiogram in acute stroke patients. Conclusion: Future studies should be based in the prehospital environment and should investigate whether undertaking an electrocardiogram in the prehospital setting affects clinical management decisions or has an association with mortality or morbidity. Conflict of interest: None declared Funding: This work was supported by School of Health Sciences PhD bursary – University of Surrey, and South East Coast Ambulance Service NHS Foundation Trust.